Core functions and forms of Bright IDEAS: A multi-methods evaluation of the adoption of an evidence-based psychosocial training program through iterative adaptation - McNeal, Demetria M.; Sahler, Olle Jane Z.; Noll, Robert B.; Fairclough, Diane L.; Voll, Megan E.; Bhat, Shubha; Morrato, Elaine H. (Frontiers in Health Services, 2022)
Background Despite efforts to widely disseminate interventions designed to increase access to quality supportive care to pediatric cancer patients and their families, many of these interventions fail to meet expectations once deployed in real-life clinical settings. This study identifies the functions and forms of Bright IDEAS: Problem-Solving Skills Training, an evidence based psychosocial intervention for caregivers of children recently diagnosed with cancer, to identify pragmatic program adaptations in its real-world clinical implementation. We compare intervention adoption before and after adaptations to the Bright IDEAS training program as part of a national training program designed to disseminate the intervention. Methods 209 pediatric psychosocial oncology practitioners representing 134 unique institutions were trained during 10 in-person 8-hour workshops (2015–2019). Functions and forms of Bright IDEAS were identified, and adaptations made to the training agenda and curriculum based on practitioner feedback following implementation in local institutions. Mixed method evaluation included longitudinal surveys at 6- and 12-months post training; and qualitative interviews among a subgroup of practitioners (N = 47) to understand and compare perspectives on intervention adoption and barriers to implementation before and after adaptations to the Bright IDEAS training program. The RE-AIM framework was used to guide dissemination evaluation. Results A total of four adaptations were tailored to the identified forms of the intervention: case studies; pre-training reading materials; training videos; and letters of institutional support from primary supervisor. Pre- and post-training adaptations to the Bright IDEAS training program were mapped to RE-AIM constructs. Quantitative findings demonstrate that adaptations appeared to improve adoption and usage overall. Conclusion This study provides insight into how contextual factors influence psychosocial practitioners' capacity to adopt, implement, and maintain Bright IDEAS in the clinical setting. This study demonstrates the use of real-time stakeholder feedback to guide intervention translation from research to practice settings.